Torque-speed relationship of the flagellar motor with dual-stator systems in Pseudomonas aeruginosa - Haolin Wu; Zhengyu Wu; Maojin Tian; Rongjing Zhang; Junhua Yuan (mBio)
ABSTRACT The single polar flagellar motor in Pseudomonas aeruginosa is equipped with two stator systems, MotAB and MotCD, both driven by H+ ions. The torque-speed relationship for flagellar motors with two stator systems has not been explored previously. In this study, we developed a method that utilizes optical trapping and fluorescence labeling to measure the torque-speed relationships for the wild-type P. aeruginosa motor with dual stators and mutant strains with a single stator system, revealing surprising differences in them. Moreover, we found that the MotAB stators exhibit slip-bond behavior in load dependence, contrasting with the catch-bond behavior of the MotCD stators and Escherichia coli stators. Further examination of the solvent isotope and pH effects on the torque-speed relationships of these stator systems provided additional insights into their dynamics. Interestingly, we discovered that the torque of the wild-type motor is similar to the combined torque of motors with MotAB or MotCD stators, indicating an additive contribution from the two stator types in the wild-type motors. These findings underscore the enhanced adaptability of P. aeruginosa to a wide range of external environments with varying load conditions.IMPORTANCEWe developed a novel method to measure the flagellar motor torque-speed relationship by trapping a swimming bacterium using optical tweezers. Using the P. aeruginosa flagellar motor as a model system to investigate motor dynamics with dual stator types, we measured the torque-speed relationships for wild-type motors with dual stator types and mutants with a single type. We found drastic differences that stem from the varying load dependencies of stator stability. These variations enable bacteria to rapidly adjust their stator composition in response to external load conditions. Interestingly, we observed that the torque of the wild-type motor is akin to the cumulative torque of motors with either stator type, indicating an additive contribution from the two stator types in wild-type motors. The methodology we established here can be readily employed to study motor dynamics in other flagellated bacteria.